The Effect of Workload and Compensation on Employee Performance Through Motivation of Functional Tax Auditor Employees at the Bekasi Middle Tax Service Office - Tito Himamora; Ismail Razak; Fajar Cahyo Utomo (The Institute of Academic Research and Publication (IARP), 2023)
The purposes of this study are 1) to analyze the effect of workload and compensation on employee motivation, 2) to analyze the effect of workload and compensation on employee performance, 3) to analyze the effect of motivation on employee performance, 4) to analyze the effect of workload and compensation on performance through employee motivation. The research was conducted on functional employees of tax auditors at the Bekasi Middle Tax Service Office. The number of samples taken in this study was 58 employees with data analysis using path analysis. The results of the study are 1) there is an effect of workload and compensation on employee motivation, 2) there is an effect of workload and compensation on employee performance, 3) there is an effect of motivation on employee performance, 4) there is an effect of workload and compensation on performance through employee motivation.